Representações literárias da escola - Mazzari, Marcus Vinícius (Estudos Avançados, 1997)
There are a number of important works that analyse the clash between adolescents or pre-adolescents and the hostile school environment in Western literature. The essay initially outlines the themes that characterise these "school stories". It then defines the characteristics of these themes and at the same time tries to determine the specificities of this literary genre through a comparison between the novels O Ateneu (1888) and Die Verwirrungen des Zöglings Törless (1906). In these strongly autobiographical works, Raul Pompéia and Robert Musil incorporate traces of behaviour and types of mentality that became evident in the historical reality some decades later into their narratives about the traumatic school experiences of Sérgio and Törless. This essay also extends the comparative study, though in a succinct way, to the "Novelle" Katz und Maus (1961), where Günter Grass makes the clash between the teenager Joachim Mahlke and his school a starting point for a radical criticism of the national socialist society. The speculative end of this essay tries to give a general view of the ideological, pedagogical and existential depths of these short narratives which apparently deal only with the ordinary drama of school life.